The Impact of Entrepreneurial Orientation in Enhancing the Managers’ Core Competencies of Charitable Institutions in Iraq - Al-Ubadi, Sanaa Abdul Raheem; Khalil, Omar Abdul-Qader; Alsomaidaee, Mustafa (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research was to identify the impact of entrepreneurial orientation with its dimensions (creative orientation, proactive orientation, acceptance of risk) in enhancing the core competencies whose dimensions include (teamwork, human capital efficiency) in the Authority of Management and investment of Sunni endowment funds (AMISEF). The research has conducted due to the importance of entrepreneurial orientation in the AMISEF, based on the importance of charitable work, preservation of endowments, development and investment, and the revival of the endowment Sunnah and its civilizational position in the renaissance of society. Since, this responsibility rests with all the administrative levels in the authority, but the choice was made at the middle administrative level, that supervises the lower level of workers, which represents the link with the higher management, and has a vision of the work mechanism, as well as the obstacles that prevent the authority from reaching an appropriate entrepreneurial direction. Thus, the research population is represented at the headquarters of the AMISEF of Management and investment of Sunni endowment funds. As for sample, it was an intentional sample of (50) managers (at the level of department directors, their assistants, and people officials). A questionnaire was developed to measure the research variables, according to some of previous scales. The Statistical Package for the Social Sciences (SPSS) was used to test the research hypotheses through appropriate statistical methods. The results showed that there was a statistically significant effect of the dimensions of the entrepreneurial orientation (including its dimensions) on the core competencies with its dimensions in AMISEF where research has conducted.